ELECTROEXTRACTION OF NICKEL FROM METHANESULFONATE LEACHING SOLUTIONS - SKNAR, YURI; SKNAR, IRYNA; BUTYRINA, TETIANA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
An important applied problem is the selective extraction of valuable components from scrap alloys of refractory metals with iron group metals containing a significant amount of rare metals. The urgency and relevance of research in this area is due to the strategic importance of these metals for the defense industry of Ukraine, since alloys based on them have unique physical and mechanical properties and are used, in particular, as structural materials in gas turbine equipment and elements of military equipment. Given that the service life of aircraft turbojet engines depends on the resource of the most important components, increasing their reliability is possible through the use of high-purity components of heat-resistant nickel-based alloys. The hydrometallurgical method of processing spent parts from such alloys is energy-saving. Nickel transferred to the solution can be isolated chemically or electrochemically. Electroextraction is the most selective method of isolating high-purity nickel from the leaching solution. To extract nickel with low internal voltages, sulfur-containing organic substances are used, which are added to the electroextraction solution. In the presented work, a new type of leaching solution based on methanesulfonic acid, the salts of which are highly soluble in an aqueous medium, was investigated. Sodium orthoarylsulfonate and saccharinate were used as sulfur-containing internal voltage reducers. It was found that the separation of nickel from the methanesulfonate solution occurs at a lower polarization compared to the sulfate solution. The effect of sodium orthoarylsulfonate in an amount of 15 mmol/l on the kinetics of nickel separation from the methanesulfonate solution is insignificant. Sodium saccharinate increases the polarization of nickel separation from the methanesulfonate solution by 100 mV already at a concentration of 0.25 mmol/l. Nickel without internal stresses was obtained from methanesulfonate solution in the presence of 15 mmol/L orthoaryl sulfonate or 0.05 mmol/L sodium saccharinate. The range of current densities for obtaining stress-free nickel in the case of sodium orthoaryl sulfonate is 2–7 A/dm2, for sodium saccharinate this range is 2–5 A/dm2
Keywords: nickel; electrowinning; recycling; methanesulfonate solution